THE INTEGRATION OF TECHNOLOGY IN ENGLISH LANGUAGE TEACHING AT UNIVERSITY LEVEL - Mamirova Gunchaoy Zahiriddin qizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This thesis examines the integration of technology in English language teaching (ELT) at the university level, with a specific emphasis on pedagogical opportunities and implementation challenges. Recent empirical studies indicate that technology facilitates seamless access to authentic language input, collaborative learning, individualized practice, and greater learner autonomy in higher education contexts. Concurrently, universities face systematic barriers such as unequal access to infrastructure, technical unreliability, limited digital competence among staff, institutional workload pressures, and the rapid pace of technological obsolescence. Using a qualitative, literature-based research design within an IMRAD structure, this paper argues that effective technology utilization depends not on the tools themselves, but on the strategic alignment of technology, pedagogy, and content knowledge. The thesis concludes that sustainable integration requires targeted teacher professional development, robust institutional support, and systematic curriculum design that treats technology as a pedagogical instrument rather than a mere replacement for traditional teaching.
Keywords: Key words: Technology integration, English language teaching, University level, Higher education, Digital pedagogy, E-learning, Blended learning, Mobile-assisted language learning (MALL), Computer-assisted language learning (CALL), TPACK framework.